Determinação do tempo de inatividade pós-aquecimento de jogadores reservas em jogos de basquetebol - Santos, Sergio Costa; Santos Pinto, Herdley Kelvin dos; Almeida, Marcos Bezerra de (2020)
In basketball, substitute athletes who enter the match only in the second quarter of the game (Q2) remain inactive for a long, but not objectively known period of time. The objective of this paper is to determine a professional basketball first quarter (Q1) elapsed time, the time-interval from the end of warming-up period to the start of the game (AQ-IP), and to the start of the second quarter (AQ-Q1), considering different tournament and competition phases. The sample was composed by 126 matches of four tournaments: Novo BasqueteBrasil (NBB 2011/2012), American Cup 2017, Eurobasket 2017 e Afrobasket 2017. Statistical analysis determined percentiles for each variable, comparing among tournaments and between competition phases (regular season vs. playoff). The results shows that Mean standard-deviation(median) of Q1, AQ-IP and AQ-Q1 (min:s) were 17:47 02:08 (14:44), 02:05 00:36 (02:08) e 20:16 02:08 (20:23), respectively. Afrobasket games' Q1 were longer than NBB's (p<0.05), although no difference between regular season and playoffs were found. We can conclude that a non-starter basketball player that checks in only at Q2 remains seated on bench longer than 20 min, regardless of the competition phase. National African teams' Q1 matches are more interrupted than Brazilian teams'.
Introdução: No basquetebol, atletas substitutos que entrem na partida apenas no segundo quarto de jogo (Q2) permanecem inativos por um longo, porém não objetivamente conhecido período de tempo. Objetivo: determinar a duração média do primeiro período (Q1) do basquetebol profissional, a duração média entre o término do aquecimento e início da partida (AQ-IP) e do segundo quarto (AQ-Q1), considerando diferentes competições e fases. Métodos: A amostra foi composta por 126 jogos de quatro competições Novo Basquete Brasil (NBB 2011/2012), American Cup2017, Eurobasket 2017 e Afrobasket 2017. Foram calculados os percentis de cada variável, além da comparação entre competições e entre fases da competição (fase classificatória e playoffs). Resultados: A média desvio-padrão (mediana) da duração de Q1, AQ-IP e AQ-Q1 (min:s) foi de 17:47 02:08 (14:44), 02:05 00:36 (02:08) e 20:16 02:08 (20:23), respectivamente. O Q1 dos jogos da Afrobasket foi mais longo que os do NBB (.<0,05), mas não houve diferença entre a fase regular e os playoffs. Conclusão: Um atleta substituto que entre na partida apenas no Q2 permanece sentado no banco de reservas por mais de 20 minutos, independentemente da fase da competição. O Q1 dos jogos de seleções africanas é mais paralisado que os do campeonato brasileiro.
Keywords: Athletic Performance; Warm-Up Exercise; Regulation; Athlete; Performance Esportiva^lpt; Exercício de Aquecimento; Regulamento; Atleta